Detected Abundances of Nuclei Relative to 26Fe for Elements 14Si through 44Ru with CALET on the International Space Station - O. Adriani; Y. Akaike; K. Asano; Y. Asaoka; E. Berti; P. Betti; G. Bigongiari; W. R. Binns; M. Bongi; P. Brogi; A. Bruno; N. Cannady; et al. (The Astrophysical Journal)
The Calorimetric Electron Telescope (CALET), launched to the International Space Station (ISS) in 2015 August and continuously operating since, measures cosmic-ray (CR) electrons, nuclei, and gamma rays. CALET, with its 27 radiation length deep Total Absorption Calorimeter, measures particle energy and allows for the measurement of spectra, secondary to primary ratios of the more abundant CR nuclei through _28 Ni, while the main charge detector can measure ultra-heavy CR nuclei through _44 Ru. The results for the abundances of elements from Z = 14 to Z = 44 relative to _26 Fe over 7.5 yr of observation are presented here and compared to previous measurements from ACE-CRIS, SuperTIGER, and HEAO-3.